Emerging Roles of LSM Complexes in Posttranscriptional Regulation of Plant Response to Abiotic Stress - Catalá, Rafael; Carrasco-López, Cristian; Perea-Resa, Carlos; Hernández-Verdeja, Tamara; Salinas, Julio (Frontiers in Plant Science, 2019)
It has long been assumed that the wide reprograming of gene expression that modulates plant response to unfavorable environmental conditions is mainly controlled at the transcriptional level. A growing body of evidence, however, indicates that posttranscriptional regulatory mechanisms also play a relevant role in this control. Thus, the LSMs, a family of proteins involved in mRNA metabolism highly conserved in eukaryotes, have emerged as prominent regulators of plant tolerance to abiotic stress. Arabidopsis contains two main LSM ring-shaped heteroheptameric complexes, LSM1-7 and LSM2-8, with different subcellular localization and function. The LSM1-7 ring is part of the cytoplasmic decapping complex that regulates mRNA stability. On the other hand, the LSM2-8 complex accumulates in the nucleus to ensure appropriate levels of U6 snRNA and, therefore, correct pre-mRNA splicing. Recent studies reported unexpected results that led to a fundamental change in the assumed consideration that LSM complexes are mere components of the mRNA decapping and splicing cellular machineries. Indeed, these data have demonstrated that LSM1-7 and LSM2-8 rings operate in Arabidopsis by selecting specific RNA targets, depending on the environmental conditions. This specificity allows them to actively imposing particular gene expression patterns that fine-tune plant responses to abiotic stresses. In this review, we will summarize current and past knowledge on the role of LSM rings in modulating plant physiology, with special focus on their function in abiotic stress responses.